Enterprise & Business Management: A Handbook for Educators, Consultants, and Practitioners - Erkollar, Alptekin (Tectum Verlag, 2020)
Organizations have always been dependent on communication, information, technology and their management. The development of information technology has sped up the importance of management information systems, which is an emerging discipline combining various aspects of informatics, information technology, and business management. Understanding the impact of information on today’s organizations requires technological and managerial views, which are both offered by management information systems.Business management is not only about generating greater returns and using new technologies for developing businesses to reach future goals. Business management also means generating better revenue performance if plans are diligently followed.It is part of business management to have an ear to the ground of global economic trends, changing environmental conditions and preferences, as well as the behavior of value chain partners. While, until now, business management and management information systems are mostly treated as independent fields, this publication takes an interest in the cooperation of the two. Its contributions focus on both research areas and practical approaches, in turn showing novelties in the area of enterprise and business management.Main topics covered in this book are technology management, software engineering, knowledge management, innovation management and social media management.This book adopts an international view, combines theory and practice, and is authored for researchers, lecturers, students as well as consultants and practitioners.